Dynamics of digital constituent outreach and engagement in linguistically divided societies: A quantitative look at the Canadian case. (1st September 2019) - Richez, Emmanuelle; Raynauld, Vincent
AbstractThis article unpacks how legislators in five Canadian provinces turn to official languages (French and English) for digital constituent outreach. In a linguistically fragmented society, use of languages is highly strategic as they can help spread information on political matters to the public and help legislators build support ahead of elections. This article first measures legislators' uses of bilingualism in the digital mediascape with the help of an index. It finds that legislators tend to be mostly unilingual in their digital constituent communications. Second, this article identifies factors influencing legislators' linguistic choices. It tests correlations between legislators' socio-demographic and political profile (e.g. gender, party affiliation, political rank) and uses of official languages. It also determines if the linguistic makeup of legislators' ridings impacts language choices. This article concludes that these variables may impact legislator's use of bilingualism depending on the province of origin and the type of online platform.